Bilirubin binding by variant albumins in Yanomama Indians. - Lorey, F W (1984)
Sera of Yanomama Indians homozygous for the common albumin allele exhibited greater total effective-binding capacities for bilirubin than did sera of individuals homozygous for the Yan-2 albumin variant in the in vitro experiments described herein. Total effective binding capacities of heterozygous samples were close to those of homozygotes for AlA. Individuals homozygous for Yan-2 might experience a higher risk of bilirubin toxicity and related disorders during the neonatal period. Further studies of binding and displacement of bilirubin by competitors, such as dietary or medicinal coumarins, might help explain the existence of these polymorphisms and the significance of phenotypic differences in binding to bilirubin.